APPROXIMATE SOLUTIONS OF GENERAL SECOND–ORDER INITIAL VALUE PROBLEMS USING DIFFERENTIAL EVOLUTION. (2017) - BAKRE, OMOLARA FATIMAH; WUSU, ASHIRIBO SENAPON; AKANBI, MOSES ADEBOWALE
No abstract available